EFFECT OF LONELINESS ON DEATH ANXIETY AMONG ELDERLY PEOPLE (International Journal of Food and Nutritional Sciences, 2022)
The simultaneous forces of industrialization and urbanization, compounded by the pervasive impact of Western lifestyles in metropolitan areas, are causing seismic transformations in India's societal environment. These changes are upending long-standing conventions and changing family arrangements. In the middle of this turmoil, the position of the elderly is changing significantly. The old pillars of respect, care, and love are quickly disappearing, which makes the elderly feel neglected.